2011
DOI: 10.1002/erv.1086
|View full text |Cite
|
Sign up to set email alerts
|

Childhood sexual and physical abuse in Spanish female undergraduates: Does it affect eating disturbances?

Abstract: After controlling for different risk factors, CSA appears to be related to an increased Weight Concern, whilst other ED attitudinal features and behaviours do not seem to be related to childhood abuse. The inverse relationship found is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 56 publications
1
19
0
5
Order By: Relevance
“…Other studies have shown mixed findings for links between a history of abuse or trauma and the severity of eating disorder symptoms [2,3,4]. Perhaps the presence of diagnoseable PTSD, examined in the present study, is a more potent predictor of bulimic severity than a history of child trauma and reflects the affective dysregulation that accompanies PTSD, but does not always accompany the experience of trauma or abuse [25,26]. Nonetheless, with the use of EMA technology in the present study, with its accompanying sensitivity to capturing behavioral events in real time, individuals with BN+PTSD engaged in a greater frequency of bulimic behaviors than those with BN only.…”
Section: Discussionmentioning
confidence: 56%
“…Other studies have shown mixed findings for links between a history of abuse or trauma and the severity of eating disorder symptoms [2,3,4]. Perhaps the presence of diagnoseable PTSD, examined in the present study, is a more potent predictor of bulimic severity than a history of child trauma and reflects the affective dysregulation that accompanies PTSD, but does not always accompany the experience of trauma or abuse [25,26]. Nonetheless, with the use of EMA technology in the present study, with its accompanying sensitivity to capturing behavioral events in real time, individuals with BN+PTSD engaged in a greater frequency of bulimic behaviors than those with BN only.…”
Section: Discussionmentioning
confidence: 56%
“…Some previous studies have found a relationship between CSA and these impulsive behaviors (Mullings, Hartley, & Marquart, 2004;Preti, Incani, Camboni, Petretto, & Masala, 2006), but others have not been able to establish this relationship. For example, some studies that have controlled the effect of other factors such as age or psychological symptomatology have not found a relationship between CSA and eating symptomatology (Villarroel et al, 2012). Other studies have found that, after controlling for parental drug or alcohol abuse, the effect of child maltreatment on excessive drinking in adulthood was not significant in women (Widom, White, Czaja, & Marmorstein, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Child abuse (CA) is a major life stressor that has important consequences for several indices of mental health in adults (Villarroel, Penelo, Portell, & Raich, 2012). More precisely, Child Sexual Abuse (CSA) is recognized within CA as one of the most traumatic experiences, which could lead to severe alterations in the health of those who suffered it.…”
mentioning
confidence: 99%
“…Childhood abuse can take many forms (Higgins & McCabe, 2001;Kent & Waller, 1998;Mazzeo & Espelage, 2002), and despite obvious potential overlaps between categories, four major variants are commonly identified; physical abuse, sexual abuse, emotional abuse, and neglect. Abuse has been linked to high levels of maladaptive CBs held in adulthood (Cecero, Nelson, & Gillie, 2004) and has also been identified as a risk factor for later eating pathology (Kent, Waller & Dagnan, 1999;Striegel-Moore, Dohm, Pike, Wilfley, & Fairburn, 2002;Villarroel, Penelo, Portell, & Raich, 2011;Waller, Corstorphine, & Mountford, 2007). However, no study has yet examined the four major abuse categories and their relationship with CBs and ED symptoms.…”
mentioning
confidence: 99%